The Neotropical taxa of the genus Dinocryptops Crabill, 1953 (Chilopoda: Scolopendromorpha) - Chagas Jr., Amazonas (Zootaxa, 2003)
Two Neotropical species, one of them divided into two subspecies, are currently ascribed to the genus Dinocrytops Crabill, 1953, and are revised here. Dinocryptops puruensis (Bücherl, 1941) and D. miersii guaraniticus (Coscarón, 1955) are synonymized with Dinocryptops miersii (Newport, 1845). A specimen from São Paulo State, Southeastern Brazil, is designated as neotype for D. miersii (Newport, 1845). Dinocryptops miersii is recorded for the first time for the Brazilian states of Minas Gerais, Espírito Santo, Distrito Federal, and Santa Catarina.